2013
DOI: 10.5194/tc-7-977-2013
|View full text |Cite
|
Sign up to set email alerts
|

Variability of light transmission through Arctic land-fast sea ice during spring

Abstract: Abstract. The amount of solar radiation transmitted through Arctic sea ice is determined by the thickness and physical properties of snow and sea ice. Light transmittance is highly variable in space and time since thickness and physical properties of snow and sea ice are highly heterogeneous on variable time and length scales. We present field measurements of under-ice irradiance along transects under undeformed land-fast sea ice at Barrow, Alaska (March, May, and June 2010). The measurements were performed wi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 45 publications
5
32
1
Order By: Relevance
“…By combining surface measurements from a sledge-based system (Hudson et al, 2012) with measurements carried out by divers beneath the ice, the complete radiation balance of the first-year sea ice system could be quantified, for a given case and stage . Similar observations were also done over landfast ice near Barrow, Alaska, but with the under-ice radiation measured from a sledge that slides along the underside of the land-fast ice, pulled with a rope (Nicolaus et al, 2013).…”
Section: Transmittance Of Sea Ice and Snowsupporting
confidence: 55%
“…By combining surface measurements from a sledge-based system (Hudson et al, 2012) with measurements carried out by divers beneath the ice, the complete radiation balance of the first-year sea ice system could be quantified, for a given case and stage . Similar observations were also done over landfast ice near Barrow, Alaska, but with the under-ice radiation measured from a sledge that slides along the underside of the land-fast ice, pulled with a rope (Nicolaus et al, 2013).…”
Section: Transmittance Of Sea Ice and Snowsupporting
confidence: 55%
“…Our results demonstrate the strong potential to estimate Antarctic ice algal biomass from transmitted under-ice irradiance spectra, in particular using NDIs. Given some degree of regional dependency for our bestperforming method (NDIs), our results suggest that this method may be more appropriate for time series measurements using moored sensors than multiregional mapping efforts (Nicolaus et al 2013. However, explanatory power might be improved through consideration of additional predictive variables (e.g.…”
Section: Discussionmentioning
confidence: 95%
“…the vertical distribution of ice algal biomass, the biomass of under-ice phytoplankton or the concentration of non-algal particles). Nicolaus et al (2013) found that the seasonal evolution of transmitted solar radiation through landfast sea ice near Barrow, Alaska, USA, exceeded the spatial variability. All 3 of the voyages considered here were carried out early in the season during spring algal biomass buildup.…”
Section: Discussionmentioning
confidence: 99%
“…The 3 known sinks for DMS are photo-oxidation, bacterial consumption and ventilation. Photooxidation should be minimal underneath the ice due to the prevailing low irradiance in general and UV radiation in particular (Winther et al 2004, Nicolaus et al 2013. DMS bacterial consumption likely takes place, but, as observed at lower latitudes, DMSconsuming bacteria generally take some time to react to a pulse in DMS, allowing a temporary buildup of the DMS reservoir.…”
Section: Response Of the Under-ice Algal And Bacterial Assemblage To mentioning
confidence: 99%